The state of interprofessional collaboration in Northern Italy: a mixed methods study. Issue 1 (January 2015) - Mischo-Kelling, Maria; Wieser, Heike; Cavada, Luisa; Lochner, Lukas; Vittadello, Fabio; Fink, Verena; Reeves, Scott
Abstract Health care systems are facing continual reorganizations in response to scientific and technological innovations as well as financial constraints. Simultaneously the rising prevalence of chronic diseases call for a kind of health care organization in which interprofessional collaboration (IPC) functions on a high level. This article describes a research project that aims to generate an empirical account of the current state of IPC in the South Tyrolean Health Trust, located in a bilingual region in northern Italy. The study will employ a sequential mixed methods' design. A survey will be followed by individual and focus group interviews. An innovative aspect of the study is that it will include participants from six different health professions (dieticians, nurses, occupational therapists, physicians, physiotherapists, and speech therapists). Qualitative data analysis will draw on the negotiated order/structural ordering approach and on the social world/arena perspective. The results are expected to generate specific recommendations to improve IPC in the South Tyrolean Health Trust and inform further research.